Strategi Public Relations Pariwisata Bali - Cahaya Putra, Kadek Dwi (Jurnal Ilmu Komunikasi, 2008)
Abstract: Bali has to maintain its image and reputation as the world leading class tourist destination. Tourism in fact is a vulnerable industry easily ruined by related issues and crises. Therefore, Public Relations (PR) with its communication strategy is highly required to maintain good relationships with related parties. This study is aimed at identifying Baliâs Public Relations positioning and setting up its PR strategies. Data and information are gained by means of questionnaire distributed to The Bali Tourism Board (BTB) with its stakeholders as an organization playing important role in Bali tourism. The data is then analyzed by SWOT (Strength Weaknesses Opportunities and Threats) analysis. It is then found that Baliâs PR positioning is on quadrant V means Stabilization/Growth. The appropriate strategies then are socializing the importance of Issue and Crisis Management, be more creative in tourism related special events, developing relationships with medias, improving tourism publicationâs quality, maintaining relationships with related tourism organization and Bali community internally.